2012
DOI: 10.1007/s00192-012-1870-4
|View full text |Cite
|
Sign up to set email alerts
|

Lower urinary tract symptoms in women with vaginal agenesis

Abstract: Women with vaginal agenesis had significant levels of urinary symptoms and to our knowledge this has not been reported before. The majority of symptoms were not altered by treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 8 publications
0
9
0
4
Order By: Relevance
“…Although some studies (Wabrek et al, 1971;Ingram, 1981), including our own research group (Callens et al, 2014), suggested that the highest gain in vaginal depth was reached within 4-6 weeks, and that the gain thereafter is minimal, it is unclear from the available data if there exists an optimal window for gaining length. Unfortunately, despite compliance, which can be increased with psychological support (Alderson and Glanville, 2004;Edmonds et al, 2012), conservative therapy can fail (Liao et al, 2011;Michala et al, 2012). No conclusions so far can be drawn on the presence or absence of the hymen relating to failure of treatment (Kimberley et al, 2012), nor whether perineal skin is different from the vagina in its elastic characteristics.…”
Section: Anatomical Successmentioning
confidence: 99%
See 2 more Smart Citations
“…Although some studies (Wabrek et al, 1971;Ingram, 1981), including our own research group (Callens et al, 2014), suggested that the highest gain in vaginal depth was reached within 4-6 weeks, and that the gain thereafter is minimal, it is unclear from the available data if there exists an optimal window for gaining length. Unfortunately, despite compliance, which can be increased with psychological support (Alderson and Glanville, 2004;Edmonds et al, 2012), conservative therapy can fail (Liao et al, 2011;Michala et al, 2012). No conclusions so far can be drawn on the presence or absence of the hymen relating to failure of treatment (Kimberley et al, 2012), nor whether perineal skin is different from the vagina in its elastic characteristics.…”
Section: Anatomical Successmentioning
confidence: 99%
“…Overall, complication rates were significantly lower within the vaginal dilation groups when compared with the different vaginoplasty techniques, being its major advantage, but should be followed-up in the longterm as well. Displacement of the bladder neck might occur during vaginal lengthening, which may affect bladder function and cause urinary symptoms (Michala et al, 2012). Also, the creation of a vagina in this fashion does not preclude vaginal disease, and cases of vaginal intra-epithelial neoplasia and vaginal carcinoma have been described (Hopkins, 1987).…”
Section: Anatomical Successmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the ACOG recommendation in 2002, we searched for literature describing non‐surgical vaginal reconstruction as the first‐line treatment in MRKH syndrome and other related conditions. The success rates were reported as 81% in 26 cases by Ismail‐Pratt et al ., 88% in 64 cases by Gargollo et al ., 78% in 32 cases by Bach et al ., 95% in 245 cases by Edmonds et al ., and 74% in 19 cases by Michala et al . In these reports, the successful vaginal length was 6–8.5 cm.…”
Section: Discussionmentioning
confidence: 92%
“…In 1938, Frank et al first reported the non-surgical method for expanding the extragenital skin using a dilator with dull edges. 5 Following the ACOG 10 In these reports, the successful vaginal length was 6-8.5 cm. The age of initiating the treatment, duration of practice, and time required for achieving the results have been variously described in the literature.…”
Section: Discussionmentioning
confidence: 95%